THEORETICAL BASIS OF ARABIC LEARNING TECHNOLOGY - Sholekhah, Maratus; Kholis Amrullah, M; Imam Fakhrurrozy, M; Mustofa, Ali (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
this article discusses Arabic Language Learning Technology. the research method uses literature with content analysis. research results: Arabic learning technology has become an increasingly important subject in today's world of education. With the development of information and communication technology, the approach to learning Arabic has changed significantly. The theoretical basis of Arabic learning technology involves the integration of traditional learning methods with modern technology, such as mobile applications, online learning platforms, and specialized learning software. This approach allows Arabic learners to learn more interactively, independently, and efficiently. In addition, the theoretical basis of Arabic learning technology also includes the concepts of learning psychology and applied linguistics. By utilizing time-tested learning theories and linguistic principles of Arabic, learning technologies can be designed more effectively. This allows Arabic teachers to create a more engaging and efficient learning experience for learners, thus improving their understanding and mastery of Arabic. By understanding the theoretical basis of this Arabic learning technology, teachers can develop more innovative and adaptive learning strategies according to the needs and development of students.